2008
DOI: 10.1007/s12205-008-0155-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of short-term stability for sea-wall structure at Kobe Airport

Abstract: Prior to the huge reclamation work for constructing Kobe Airport, the sea-wall structure resting on a 30m-thick soft Holocene clay layer in the 16m-deep sea was constructed at stages over the period of three years. Regarding the design of short-term stability of the sea-wall structure, the ratio of undrained shear strength of the normally-consolidated seabed clay to in-situ yield stress was estimated to take the value of 0.35 in order to satisfy the factor of safety in excess of 1.3. This design strength in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In this study, we focus on the shear strength of the soil elements induced by seismic motion. It is known that the shear strength of soil elements with elasto-viscoplastic properties depends on the shear rate (Ovando-Shelley 1995;Duttine et al 2008;Shibuya et al, 2008;Kokusho 2019). Kameda (2022) have reported rheological properties for the Ta-d soil type investigated in this study.…”
Section: 5mmentioning
confidence: 65%
“…In this study, we focus on the shear strength of the soil elements induced by seismic motion. It is known that the shear strength of soil elements with elasto-viscoplastic properties depends on the shear rate (Ovando-Shelley 1995;Duttine et al 2008;Shibuya et al, 2008;Kokusho 2019). Kameda (2022) have reported rheological properties for the Ta-d soil type investigated in this study.…”
Section: 5mmentioning
confidence: 65%
“…50 have been suggested for different types of soils in numerous studies (e.g. Chung et al, 2007;Jardine and Hight, 1987;Karlsson and Viberg, 1967;Kim et al, 2009;Ladd, 1991;Larsson, 1980;Mayne, 1980;Mayne and Mitchell, 1988;Nicholson and Jardine, 1981;Shibuya et al, 2008;Suzuki and Yasuhara, 2007;Tanaka, 1994;Watabe et al, 2002). From these studies it can be concluded that the s u =ó 9 p ratio varies with soil type.…”
Section: Introductionmentioning
confidence: 91%
“…Several recently published studies have adopted total stress analyses to evaluate stability during staged construction (e.g. Shibuya et al, 2008;Watabe et al, 2002). A total stress analysis based on the initial undrained shear strength s u0 in the clay would in most cases be conservative (i.e.…”
Section: Introductionmentioning
confidence: 99%